Quantum Oncology: The Applications of Quantum Computing in Cancer Research. - Li, Jiaran; Li, Li; Liu, Ning; Xu, Fuhao; Hu, Tao; Yuan, Shuanghu (Journal of Medical Systems, 2025)
A global technological race is underway to develop increasingly powerful and precise quantum computers. As a transformative computing paradigm, quantum computing offers the potential for exponentially accelerating specific algorithms, thereby providing the necessary computational power to process vast amounts of data. In light of the challenges classical computing faces with the complexity and volume of oncology data, we introduce the concept of "quantum oncology" and explore its potential applications throughout the cancer care continuum. Additionally, we address several challenges and potential solutions for integrating quantum computing into oncology research. By illuminating these issues, we aim to deepen the understanding of quantum computing's potential in oncology and advocate for multidisciplinary collaboration to propel the advancement of precision oncology. Clinical Trial Number: Not applicable.